1996
DOI: 10.1056/nejm199611283352227
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia, Physician-Assisted Suicide, and Other Medical Practices Involving the End of Life in the Netherlands, 1990–1995

Abstract: Since the notification procedure was introduced, end-of-life decision making in the Netherlands has changed only slightly, in an anticipated direction. Close monitoring of such decisions is possible, and we found no signs of an unacceptable increase in the number of decisions or of less careful decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
241
2
12

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(261 citation statements)
references
References 11 publications
6
241
2
12
Order By: Relevance
“…Previous studies identified substantial biases during the end-of-life decision-making process [4,11,14,15]. These biases were related to the patients, the family, or the ICU physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies identified substantial biases during the end-of-life decision-making process [4,11,14,15]. These biases were related to the patients, the family, or the ICU physicians.…”
Section: Discussionmentioning
confidence: 99%
“…These biases may account for considerable practice differences that cannot be explained by routinely collected information. Sources of bias may be patient related (e.g., patient unwilling to receive life support or be dependent on vasopressors), family related (e.g., cultural factors, religion, and religiosity [4,14,15]), and clinician related (e.g., gender, role, specialty, and time working in ICUs [16][17][18][19][20]). In addition, treatments are more likely to be withdrawn if they are expensive or scarce or if they support noniatrogenic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch Government took the bull by the horns in 1990, by requesting the first of a series of comprehensive, nationwide, research articles into euthanasia and other medical decisions concerning the end of life [48]. It is time for the British Government to urgently instigate a study of the need for PAS, in the whole of the UK, for the terminally ill, already on palliative care and whose life has become unbearable to them, including those with advanced dementia and advanced neurodegenerative diseases who have a valid 'advance directive' which clearly describes the stage at which they would like assistance to die.…”
Section: Recommendationsmentioning
confidence: 99%
“…Under Dutch legislation euthanasia and physician-assisted suicide are technically crimes, but through an amendment to the Burial Act physicians are granted immunity from prosecution if they adhere to certain conditions. 2 The Royal Dutch Pharmaceutical Association has issued guidelines for pharmacists who receive requests to dispense drugs for euthanasia or physician-assisted suicide. The guidelines, however, have no legal status.…”
Section: Physician-assisted Death and Pharmacy Practice In The Nethermentioning
confidence: 99%